KERAGAAN PERTUMBUHAN VEGETATIF DAN REPRODUKTIF HIBRIDA JAGUNG PERSILANGAN GALUR INBRIDA MUTAN (M4) PADA LATOSOL DARMAGA - Rustikawati Rustikawati; Catur Herison; Surjono H. Sutjahjo (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2010)
[VEGETATIVE AND REPRODUCTIVE PERFORMANCES OF MAIZE HYBRIDS GENERATED FROM INBRED MUTANTS (M4) ON DARMAGA LATOSOL]. The development of hybrids from local germplasms are extensively done as alternative to the expensive imported hybrid seeds. The farthest genetic distance of parental lines is required to develop the best hybrids. The objective of this study was to compare the vegetative and reproductive performances of hybrids generated from crosses of M4 inbred lines, generated from the selected gamma irradiated mutants. Twenty eight hybrids derived from diallel crosses of M4 inbred lines and a check hybrid variety (NK33) were evaluated on Darmaga latosol. The results showed that all hybrids had lower performances on vegetative and reproductive characters compared to NK33. However, based on the selection index involving all characters, hybrids of G3 x G8, G6 x G8, and G8 x G6 with the index values of 9.45, 7.85, and 6.72, respectively, performed better than or similar to NK33.